Medicinal Uses and Pharmacological Activity of Dodonaea Viscose: A Literature Review - Rajaratnam, T.; Sathiyaseelan, V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2016)
Dodonaea viscose belongs to family Sapindaceae. It is an ever green small tree and used traditionally in the treatment of rheumatism, gout, swelling, burns, scalds, wound, snake bite and stomach disorders. The objective of this study is to identify the medicinal uses and pharmacological activity of this plant. Knowledge on medicinal uses of D. viscosais limited among Sri Lankan physicians. Normally they use this plant as poultice for 'Keelvaayu' (rheumatic) conditions. Data was gathered from Siddha and traditional medical books, journals and internet. Extract of the plant has wound healing and stimulant activity in the nervous system. A wide range of chemical constituents such as albumin, tannin, saponin, amorphous alkaloid have been isolated especially from the leaves of the plant. Action of this plant is tonic, sudorific, alterative, hypoglycemic and febrifuge. Siddha text books contain small amount of chemicals and pharmacological actions of this plant, but now the experiments of D. viscosa has revealed the anti- microbial, anti-fungal and hypoglycemic actions. Further experiments has to be done on the each part of this plant is important to identify more chemical constituents and pharmacological actions to treat many diseases. Before recommending it for clinical uses in these conditions, need to conduct experimentl trial to prove its efficacy.
Keywords: Dodonaea viscosa; Pharmacological activity; Medicinal uses